Generation and observation of fast deuterium ions and fusion-born alpha particles in JET D−3He plasmas with the 3-ion radio-frequency heating scenario. (30th October 2020) - Nocente, M.; Kazakov, Ye.O.; Garcia, J.; Kiptily, V.G.; Ongena, J.; Dreval, M.; Fitzgerald, M.; Sharapov, S.E.; Stancar, Z.; Weisen, H.; Baranov, Y.; Bierwage, A.; et al.
Abstract: Dedicated experiments to generate energetic D ions and D − 3 H e   fusion-born alpha particles were performed at the Joint European Torus (JET) with the ITER-like wall (ILW). Using the 3-ion D − ( D N B I ) − 3 H e radio frequency (RF) heating scenario, deuterium ions from neutral beam injection (NBI) were accelerated in the core of mixed D − 3 H e   plasmas to higher energies with ion cyclotron resonance frequency (ICRF) waves, in turn leading to a core-localized source of alpha particles. The fast-ion distribution of RF-accelerated D-NBI ions was controlled by varying the ICRF and NBI power ( P I C R F ≈ 4–6 MW, P N B I ≈ 3–20 MW), resulting in rather high D-D neutron (≍ 1 × 10 16 s −1 ) and D − 3 H e   alpha rates (≍ 2 × 10 16 s −1 ) at moderate input heating power. Theory and TRANSP analysis shows that large populations of co-passing MeV-range D ions were generated using the D − ( D N B I ) − 3 H e 3-ion ICRF scenario. This important result is corroborated by several experimental observations, in particular gamma-ray measurements. The developed experimental scenario at JET provides unique conditions for probing several aspects of future burning plasmas, such as the contribution from MeV range ions to global confinement, but without introducing tritium. Dominant fast-ion core electron heating with T i ≈ T e and a rich variety of fast-ion driven Alfvén eigenmodes (AEs) were observed in these D − 3 H e   plasmas. The observed AE activities do not have a detrimental effect on the thermal confinement and, in some cases, may be driven by the fusion born alpha particles. A strong continuous increase in neutron rate was observed during long-period sawteeth ( > 1 s), accompanied by the observation of reversed shear AEs, which implies that a non monotonic q profile was systematically developed in these plasmas, sustained by the large fast-ion populations generated by the 3-ion ICRF scenario.